2004
DOI: 10.1080/13651500410005720
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized single-blind, multicenter trial comparing the efficacy and safety of paroxetine with and without quetiapine therapy in depression associated with anxiety

Abstract: OBJECTIVE To evaluate quetiapine as an adjunct to paroxetine in patients with comorbid depression and anxiety. METHOD Prospective, multicenter, single-blind trial of patients with DSM-IV major depression and associated anxiety, who were randomized to an 8-week treatment with paroxetine alone (n=54) or paroxetine+quetiapine (n=58). Quetiapine was dosed to 200 mg/day and paroxetine to 60 mg/day, as required. RESULTS Decrease in HAM-A scores was significantly greater in the combined therapy group than with paroxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…While this is the first study to extensively examine the efficacy of adjunctive quetiapine in GAD, the results support a recently published letter demonstrating the efficacy of quetiapine and risperidone monotherapy in the treatment of 36 patients with GAD or GAD with comorbid panic disorder (Galynker et al, 2005), along with previous publications that suggest that quetiapine is capable of reducing symptoms and improving quality of life in patients with a range of psychiatric disorders (Bogan et al, 2005;Brawman-Mintzer et al, 2006;Denys et al, 2004;Devarajan et al, 2006;Doree et al, 2004;Hamner et al, 2003;Schutters, Van Megen, & Westenberg, 2005;Yargic et al, 2004). The efficacy of antipsychotic augmentation of traditional therapies has been demonstrated in two small, double-blind, placebo-controlled studies of adjunctive olanzapine and risperidone (Brawman-Mintzer et al, 2005;McIntyre, Gendron, & McIntyre, 2007;Pollack et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While this is the first study to extensively examine the efficacy of adjunctive quetiapine in GAD, the results support a recently published letter demonstrating the efficacy of quetiapine and risperidone monotherapy in the treatment of 36 patients with GAD or GAD with comorbid panic disorder (Galynker et al, 2005), along with previous publications that suggest that quetiapine is capable of reducing symptoms and improving quality of life in patients with a range of psychiatric disorders (Bogan et al, 2005;Brawman-Mintzer et al, 2006;Denys et al, 2004;Devarajan et al, 2006;Doree et al, 2004;Hamner et al, 2003;Schutters, Van Megen, & Westenberg, 2005;Yargic et al, 2004). The efficacy of antipsychotic augmentation of traditional therapies has been demonstrated in two small, double-blind, placebo-controlled studies of adjunctive olanzapine and risperidone (Brawman-Mintzer et al, 2005;McIntyre, Gendron, & McIntyre, 2007;Pollack et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…The efficacy of augmentation therapy against anxiety and depressive symptoms in post-traumatic stress disorder, obsessivecompulsive disorder, and treatment-resistant depression has also been demonstrated with a range of atypical antipsychotics, including quetiapine (Bogan, Koran, Chuong, Vapnik, & Bystritsky, 2005;Denys, de Geus, Van Megen, & Westenberg, 2004;Devarajan, Ali, & Dursun, 2006;Doree et al, 2004;Hamner, Deitsch, Brodrick, Ulmer, & Lorberbaum, 2003;Yargic et al, 2004), aripiprazole (Worthington, Kinrys, Wygant, & Pollack, 2005), olanzapine (Bystritsky et al, 2004;Weiss, Potenza, McDougle, & Epperson, 1999) and risperidone (Li et al, 2005). Given that atypical antipsychotics have been shown to be an effective adjunctive treatment for anxiety and depression in such a diverse range of psychiatric conditions, it is not surprising that there is a growing interest in using these agents in the treatment of GAD.…”
mentioning
confidence: 94%
“…In addition, quetiapine monotherapy and olanzapine alone, and in combination with fluoxetine, were effective in studies of bipolar depression [Calabrese et al, 2005;Tohen et al, 2003] and, more recently, quetiapine monotherapy has demonstrated efficacy in the treatment of anxiety symptoms in patients with bipolar I depression [Hirschfeld et al, 2006]. In clinical practice, the atypical antipsychotics are widely used as augmentation therapy in patients with treatmentresistant major depressive disorder [Ostroff and Nelson, 1999;Galynker et al, 2005;Yargic et al, 2004;Pathak et al, 2005;Pitchot and Ansseau, 2001;Papakostas et al, 2005]. Furthermore, there is some indication that atypical antipsychotics have efficacy in the treatment of anxiety symptoms, suggesting their possible clinical utility in major depression and comorbid anxiety [Barnett et al, 2002;Hamner et al, 2003;Adson et al, 2004;Galynker et al, 2005;Schutters et al, 2005;Worthington et al, 2005].…”
Section: Introductionmentioning
confidence: 98%
“…Esses resultados são compatíveis com estudos anteriores que sugeriram que a quetiapina tem um espectro amplo de ação, tendo utilidade tanto no tratamento da depressão bipolar em monoterapia 19,20 como na depressão unipolar, como coadjuvante de ISRS/venlafaxina [21][22][23] .…”
Section: Quetiapinaunclassified